Veiling in fashion: space and the hijab in minority communities - Almila, Anna-Mari (Dress cultures, 2019)
"Enters the worlds of women who wear the hijab, both as an aspect of their religious observance and community belonging, and as a fashion statement, drawing upon global Islamic fashion industry. Anna-Mari Almila uses rich ethnographic investigation of everyday veiling practices among Muslim women in the city of Helsinki as a lens through which to reflect on and advance understanding of matters concerning Muslim dress in international Muslim minority contexts. Almila provides an innovative approach to studying veiling by connecting varied realms of practice, demonstrating how domains such as fashion, materiality, city spaces, private life, religious beliefs, and cosmopolitan social conditions are all tightly bound up together in ways that only a sensitive multi-disciplinary approach can reveal"--